A gilded lady - Camden, Elizabeth, 1965- (Camden, Elizabeth, 1965- Hope and glory, 2020)
"In 1900, secretary to the first lady of the United States, Caroline Delacroix is at the pinnacle of high society--but is hiding a terrible secret. Agent Nathaniel Trask must battle his growing love for her as the threat to the president rises and they face adventure, heartbreak, and danger."--